Pelatihan Dan Pemberdayaan Ibu-Ibu Pkk Untuk Pencegahan Stunting Di Desa Sekardadi Kabupaten Bangli Tahun 2024 - Arini, NI Wayan; Gama, I Ketut; Marhaeni, Gusti Ayu; Wiardani, Ni Komang; Rusminingsih, Ni Ketut; Widhya HS, Cokorda Dewi (Poltekkes Kemenkes Denpasar, 2025)
Short toddlers (stunting) is a chronic nutritional problem caused by a lack of nutritional intake over a long period of time which results in factors that provide food that does not meet the nutritional needs of children. The occurrence of stunting in toddlers is caused by various factors. The direct cause is a lack of food intake and the presence of infectious diseases. Other causes are lack of maternal knowledge, wrong parenting patterns and poor hygiene and sanitation. The objectives of the Sustainable Regional Development Program are to: Increase knowledge about nutrition, especially nutrition for pregnant women to prevent stunting and Improve skills in making nutritious food using local ingredients available in the area.The results of this community service were that the percentage of PKK women's knowledge level before education had the most adequate criteria 48 people (90.57%). After education, the most are in good criteria 45 people (84.90%). The average knowledge score of PKK mothers before being given education was 66, including sufficient criteria. After education, the average score increased to 77.3, including good criteria. There was an increase in knowledge and skills after training. So that the knowledge and skills gained during the training can be applied in everyday life. Tempe Labu Siam Nugget and Lato Dimsum, can be made in various ways such as making crispy nuggets so that children don't get bored